Citizens' guide to Congress (CRTS, 1992)
"The Citizen's Guide to Congress aims to provide groups and individuals greater access and knowledge about the dynamics of Congress. This is widely recognized as key to enhancing people's participation in the legislative process. This manual features the Philippine legislative, a discussion of the structures and processes involved in both House of Representatives and the Senate of the Philippines. A discussion of the important divisions and their descriptions are presented in "where to get what in congress" data." A clearer picture of the legislative flow chart. It also provides directories of members, committee memberships, secretariat, list of party affiliations and a directory of legislative liaison, offices of the executive branch. Each directory is listed alphabetically for easy reference.